Multiwavelength Brillouin fibre laser in two-mode fiber - H., Ahmad; Sakeh, S. N. A.; Muda, Z.; Zulkifli, Mohd Zamani; Harun, S. W. (Taylor and Francis Ltd., 2017)
In this paper, a multiwavelength two-mode Brillouin fibre laser generated by two-mode optical fibre (TMOF) is proposed and demonstrated experimentally. The system comprises a 500 m long TMOF. A tunable laser source amplified by a high power erbium doped fibre amplifier acts as the Brillouin pump (BP) followed by a single mode fibre Bragg grating as a reflector in the cavity with a centre wavelength of 1544 nm. The BP is observed in the superposition of LP01 and LP11 modes in the fewmode fibre. The set-up is capable of generating a maximum of 12 clearly defined Stokes lines at the pump power of 28.6 dBm, spanning from 1543.88 to 1544.92 nm.